Caracterización del estrés laboral en profesores de la Universidad Central “Marta Abreu” de Las Villas, próximos a defensa de tesis doctoral - Beltrán Ruiz, Lianys (Universidad Central “Marta Abreu” de Las Villas, 2010)
With the objective of characterizing the labor stress in professors of the Central University "Marta Abreu" of Villa Clara who are close to defense of doctoral thesis. An exploratory-descriptive experimental study of traverse type was carried out, in the period understood between January and May of the 2011. The sample was conformed by 20 internal applicants, by means of a sampling intentional non-probabilistic. For the execution of the objectives of the research the signs and symptoms associated to the labor stress were determined, the presence of emotional states in the applicants, the main confrontation styles before the labor stress as well as the exploration of the syndrome of Burnout. The techniques employed were the semi-structured interview, Interviews clinic centered in questions on stress, Questionnaire of signs associated to the stress, Questionnaire of confrontation styles, Self experiences, Inventory of Situations and Answers of Anxiety (ISRA-B), Test of Zung and Conde, Inventory of Expression of the Anger State-feature (STAXI - 2), Exam of labor satisfaction and the Brief Questionnaire of Burnout (CBB). The prosecution of the data was carried out in a qualitative and quantitative way by means of the statistical package SPSS version 13.0.The obtained results they demonstrate the presence of labor stress in the professors through signs and symptoms so much physical, social as emotional and around 20% of them they are experiencing the syndrome of Burnout. In spite of the above-mentioned the same ones generally use such confrontation styles as the positive reappraisal, the planning, the search of social support, the self control and the confrontation. Still when they present negative emotional reactions before the stress such as anxiety, the anger and the depression, these reactions are manifested in normal levels in most of the professors.
Keywords: Estrés Laboral; Síndrome de Burnout; Profesorado; Work Stress; Burnout Syndrome; Professorate